Registered Replication Report: Dijksterhuis and van Knippenberg (1998). (March 2018) - O'Donnell, Michael; Nelson, Leif D.; Ackermann, Evi; Aczel, Balazs; Akhtar, Athfah; Aldrovandi, Silvio; Alshaif, Nasseem; Andringa, Ronald; Aveyard, Mark; Babincak, Peter; Balatekin, Nursena; Baldwin, Scott A.; et al.
Dijksterhuis and van Knippenberg (1998) reported that participants primed with a category associated with intelligence ("professor") subsequently performed 13% better on a trivia test than participants primed with a category associated with a lack of intelligence ("soccer hooligans"). In two unpublished replications of this study designed to verify the appropriate testing procedures, Dijksterhuis, van Knippenberg, and Holland observed a smaller difference between conditions (2%–3%) as well as a gender difference: Men showed the effect (9.3% and 7.6%), but women did not (0.3% and −0.3%). The procedure used in those replications served as the basis for this multilab Registered Replication Report. A total of 40 laboratories collected data for this project, and 23 of these laboratories met all inclusion criteria. Here we report the meta-analytic results for those 23 direct replications (total N = 4, 493), which tested whether performance on a 30-item general-knowledge trivia task differed between these two priming conditions (results of supplementary analyses of the data from all 40 labs, N = 6, 454, are also reported). We observed no overall difference in trivia performance between participants primed with the "professor" category and those primed with the "hooligan" category (0.14%) and no moderation by gender.